Kinerja Pemerintah dalam Rehabilitasi dan Rekonstruksi Kawasan Rawan Bencana (KRB) di Kabupaten Magelang - Khoirunnisa, Syifa Azmy; Warsono, Hardi; Suryaningsih, Margaretha (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Rehabilitation and reconstruction is one effort contained in the disaster management cycle after mitigation and emergency response. Rehabilitation and reconstruction of post-disaster to be a need of the affected community disaster. Disaster management organizers in Magelang District in general is Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Magelang, and in particular for the rehabilitation and reconstruction activities organized by sector of Rehabilitation and Reconstruction. BPBD Kabupaten Magelang has a vision